SISTEM PAKAR DIAGNOSIS DINI PENYAKIT LEUKIMIA MENGGUNAKAN METODE FORWARD CHAINING(STUDI KASUS (RSUD) RADEN MATTAHER JAMBI) - Huda Aminnudin, Fattachul; Gunawan, Satria (LP2M Universitas Nurdin Hamzah, 2020)
Research and development carried out on Leukemia aims to produce an alternative in handling leukemia which has been carried out by doctors. This research methodology uses a waterfall model with steps 1). Analyzing the System, 2). System Design, 3). Input, Process and Output, 4). Program Testing, 5). Product Results and Revisions, 6). Final Products, 7 ). Product Dissemination, also supported by data flow diagrams that illustrate the description of the system being built. This research resulted in an application of an expert system in handling web-based leukemia. This application is designed using PHP and MySQL programming languages with several display designs that make it easy for users to use it as a tool in detecting leukemia before being treated by a doctor.